Evaluating HR management strategies for recruiting and retaining IT professionals in the U.S. federal government. - Mastracci SH (Public Personnel Management)
Public personnel management research and practices increasingly focus on creative human resource management (HRM) strategies for recruiting individuals with information technology (IT) expertise and retaining employees with institutional knowledge, particularly in light of impending retirements. Some agencies face unique workforce demographic challenges, while others face shifts in missions or technologies. For these reasons, the U.S. Office of Personnel Management relaxed some regulations to allow federal agencies to meet their staffing needs. This article presents an evaluation of the effectiveness of creative HRM strategies during the late 1990s, when federal agencies sought to hire and keep IT professionals to do Year 2000 conversions.